Work discipline and corporate training in modernising large companies in Argentina. (1st July 2011) - ,
Abstract : The processes that have reinstalled and consolidated corporate hegemony over work have generated exclusion, an increase in preferential treatment and fragmentation among workers. During the 1990s, and especially as a result of the deep crisis that originated in the early 2000s in Agentina, a new situation has emerged, bringing into being a new labour/professional order and new disciplinary patterns at work, aimed at developing new subjectivities among workers. In this situation, corporate systems have been introduced based on the ''continuous improvement'' doctrine. Drawing on recent research in large automotive, iron and steel and hydrocarbon production companies settled in Argentina, this article analyses the control and work discipline devices that prevail in this system and focuses on the relationships between these devices and corporate training processes. An environment is emerging in which a new mindset is being imposed, which is analysed here. In particular, the article investigates how corporate systems use training as part of their strategy to achieve corporate hegemony over work. Finally, it focuses on the limits of these corporate systems and the tensions within them. It also studies the views of workers regarding these modernisation policies, view which are significant because they express the tensions resulting from the implementation of the new corporate systems.